Ethics of Touch – axiological model of therapeutic relation in physiotherapy - Alicja Przyłuska-Fiszer; Agnieszka Wójcik (Analiza i Egzystencja, 2020)
Ethics of Touch – axiological model of therapeutic relation in physiotherapy Abstract Ethics of the physiotherapist profession constitutes a relatively new area of bioethical considerations. National and international codes of physiotherapists’ professional ethics formulate ethical standards of the profession by referring to patients’ rights and basic bioethical principles and values common to all medical professions. The growing number of bioethical publications considering philosophical and ethical aspects of human corporeality in medicine hardly ever raise moral, emotional and psychological problems connected with physiotherapists’ use of touch as a tool for diagnosis and therapy application. There is also noticed a lack of discussion on ethical values which are of particular importance in the context of physiotherapeutic intervention. The aims of the paper: 1) Presentation of morally significant features of the physiotherapist-patient relation, which distinguish it from other therapeutic relations in medicine; 2) Analysis of the importance of body, intimacy and touch in the context of physiotherapist’s work, particularly of the moral meaning of touch and the risk of patient’s psychological and emotional boundaries violation; 3) Presentation of the initial axiological model of a therapeutic relation in physiotherapy, which will be verified through qualitative and quantitative research conducted by an interdisciplinary research team consisting of a psychologist, sociologist, educator, bioethicist and physiotherapists .